Modified nanocellulose aerogel as well as preparation method and application thereof
By preparing modified nanocellulose aerogels, the combination of vinyl trimethoxysilane and oxidized cellulose nanofibers is solved by solving the problem that nanocellulose aerogels are limited in their hydrophilicity and flammability in oil-water separation, and high efficiency oil-water separation, good flame retardant performance and low thermal conductivity are achieved.
Patent Information
- Application Number
- CN202510078364.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-22
AI Technical Summary
The application of nanocellulose-based aerogels in oil-water separation is limited by their hydrophilicity, porosity and low density, and their flammability and difficulty in extinguishing fire.
By modifying nanocellulose aerogel, a polymer including vinyl trimethoxysilane and oxidized cellulose nanofibers and oxidized cellulose nanofibers are used to adjust the pH using acid and alkali, forming a gel product and lyophilizing and heat-drying to obtain a modified nanocellulose aerogel with hydrophobicity, flame retardant and low thermal conductivity.
It has achieved efficient application of modified nanocellulose aerogel in oil-water separation, especially good adsorption performance for heavy oil, and has good flame retardant properties and low thermal conductivity and good thermal insulation performance.
Smart Images

Figure CN119859312A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a modified nanocellulose aerogel and a preparation method and application thereof. Background Art
[0002] At present, a variety of separation methods for oil-water mixtures have been developed, such as membrane separation, biodegradation, skimmers, and adsorption separation. Among them, physical adsorption is considered to be a very practical method due to its advantages such as high separation efficiency, low cost, reusable adsorbent, and environmental friendliness (no secondary pollution).
[0003] Nanocellulose-based aerogels are known for their hierarchical porosity and versatility. Their attractive properties include environmental friendliness, low density, high specific surface area, flexibility, and low thermal conductivity, making them excellent in thermal management materials in battery modules and the construction industry. However, despite the excellent performance shown by nanocellulose-based aerogels, there are still some major challenges that need to be addressed, such as the good hydrophilicity of nanocellulose-based aerogels, which limits their application in oil-water separation. In addition, nanocellulose-based aerogels are porous and have low density, making them easy to burn and difficult to self-extinguish when exposed to fire. A large amount of smoke and dust will be produced during combustion, making it difficult to extinguish the fire.
[0004] CN104710647A discloses a method for preparing a super-hydrophobic cellulose aerogel and its application in oil pollution treatment. The preparation method comprises the following steps: (1) preparing a cellulose solvent; (2) preparing a cellulose solution; (3) preparing a cellulose hydrogel; (4) preparing a cellulose aerogel; (5) cold plasma hydrophobic modification, drying the obtained cellulose aerogel to remove moisture, and hydrophobically modifying it using a cold plasma modification device; placing the cellulose aerogel on a sample rack, evacuating, and when the vacuum reaches the lowest point, filling a modifier medium into a reactor; when the vacuum reaches a constant value, discharging at a power of 60 to 250 W and a time of 1 to 15 minutes to obtain a super-hydrophobic cellulose aerogel; wherein the modifier is mainly selected from organic silanes, including trimethylchlorosilane, methyltrichlorosilane, perfluorosilane, methyltrimethoxysilane, dimethylsilanol or trialkoxysilane. The cellulose aerogel obtained by the preparation method has an adsorption capacity of less than 20 g / g for pump oil, peanut oil and diesel.
[0005] CN111253615A discloses a method for preparing a super-hydrophobic organosilicon aerogel by drying at room temperature and pressure, comprising the steps of: (1) mixing hydrogenated silicone oil, component A and a catalyst and heat-insulating at 40-70°C to obtain a gel precursor; component A is vinyl alkoxysilane and / or propenyl alkoxysilane; (2) adding an organic solvent, water and an alkaline catalyst to the gel precursor, stirring evenly and heat-insulating at 70-90°C to obtain a wet gel; (3) washing the wet gel with a washing solvent to remove the original solvent and unreacted molecules, then washing the wet gel again with a low surface energy solvent, and finally drying at room temperature and pressure to obtain a super-hydrophobic organosilicon aerogel. The organosilicon aerogel obtained by this preparation method does not specifically involve the amount of oil adsorption.
[0006] CN118750909A discloses a method for efficient oil-water separation using high-strength super-hydrophobic aerogel. The method includes the steps of using high-strength super-hydrophobic-super-oleophilic aerogel as an oil-water separation material for separation; the high-strength super-hydrophobic-super-oleophilic aerogel is prepared according to the method including the following steps: S1, preparing a silicone waterproofing agent solution of cellulose nanofibers; S2, adding polyurethane and aramid fiber to the silicone waterproofing agent solution, stirring; S3, adding hydrophobic silica to the solution treated in step S2, homogenizing to obtain a suspension; S4, injecting the suspension into a mold, and performing directional freezing; S5, freeze-drying the frozen sample obtained in step S4, and then placing it in an oven at room temperature or with water added. The aerogel obtained by this method has a low adsorption capacity for chloroalkanes. In addition, the method uses more components and the steps are slightly cumbersome.
[0007] CN113578286A discloses an adsorption material and its preparation method and application, wherein the adsorption material comprises 0.16-0.18 parts by weight of nanofibers and 0.2-0.8 parts by weight of polyaryletherketone; wherein the nanofibers are selected from cellulose nanofibers, nanocellulose whiskers or microfibrillated cellulose. The aerogel adsorption material obtained by the method can be suitable for removing aromatic hydrocarbon pollutants in water, especially having a high adsorption efficiency for diphenylamine. Summary of the invention
[0008] One object of the present invention is to provide a modified nanocellulose aerogel, which has good hydrophobicity and can be used for oil-water separation, especially has good adsorption performance for heavy oils such as chlorinated alkanes. Further, it has good flame retardant properties. In addition, its thermal conductivity is low. Another object of the present invention is to provide a method for preparing the modified nanocellulose aerogel as described above. Another object of the present invention is to provide a use of the modified nanocellulose aerogel as described above.
[0009] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0010] In one aspect, the present invention provides a modified nanocellulose aerogel, which is formed from a raw material including a polymer represented by formula (1) and oxidized cellulose nanofibers, wherein the mass ratio of the polymer represented by formula (1) to the oxidized cellulose nanofibers is denoted as m, and 1≤m<10;
[0011]
[0012] In formula (1), n is a natural number of 70 to 105, and Me is a methyl group.
[0013] According to the modified nanocellulose aerogel of the present invention, preferably, the oxidized cellulose nanofibers have a structure as shown in formula (2):
[0014]
[0015] In formula (2), y is a natural number ranging from 50 to 1000.
[0016] The modified nanocellulose aerogel according to the present invention is preferably characterized in that its contact angle is greater than or equal to 100°.
[0017] On the other hand, the present invention also provides a method for preparing the modified nanocellulose aerogel as described above, comprising the following steps:
[0018] 1) placing the polymer represented by formula (1) and the oxidized cellulose nanofiber suspension in an alkane solvent to mix to obtain a mixture;
[0019] 2) adjusting the pH value of the mixture to less than 7 with an acid to obtain an emulsion;
[0020] 3) adjusting the pH value of the emulsion to be greater than or equal to 8 with an alkali, and allowing to stand to form a gel product;
[0021] 4) freeze-drying the gel product to obtain a freeze-dried product; heating and drying the freeze-dried product to obtain a modified nanocellulose aerogel.
[0022] According to the preparation method of the present invention, preferably, in step 1), the polymer represented by formula (1) is obtained by reacting vinyltrimethoxysilane in the presence of tert-butyl peroxide; wherein the reaction is carried out in a hydrothermal autoclave, the reaction temperature is 100-150°C, and the mass ratio of tert-butyl peroxide to vinyltrimethoxysilane is 1:8-15.
[0023] According to the preparation method of the present invention, preferably, step 1) comprises the following specific steps:
[0024] Polyvinyl trimethoxysilane, oxidized cellulose nanofiber suspension and water are placed in an alkane solvent and mixed to obtain a mixture; wherein the mass concentration of the oxidized cellulose nanofiber suspension is 1-2wt%; and the alkane solvent is selected from C5-C10 alkanes.
[0025] According to the preparation method of the present invention, preferably, in step 2), the acid is selected from hydrochloric acid, sulfuric acid or nitric acid; in step 3), the base is a quaternary ammonium base.
[0026] According to the preparation method of the present invention, preferably, in step 4), the freeze-drying temperature is less than -30°C, and the heating drying temperature is greater than or equal to 45°C.
[0027] According to the preparation method of the present invention, preferably, step 4) is specifically selected from any one of the following steps:
[0028] (a) placing the gel product in a mold, placing the mold above a freezing platform so that the heat conduction direction for freezing the gel product is in a vertical direction, and freeze-drying the gel product below -50°C to obtain a freeze-dried product; heating and drying the freeze-dried product to obtain a unidirectionally frozen modified nanocellulose aerogel;
[0029] (b) placing the gel product directly in a freezing tank having an upper opening so that the heat conduction direction for freezing the gel product is vertical and horizontal, and freeze-drying the product below -50°C to obtain a freeze-dried product; heating and drying the freeze-dried product to obtain a bidirectionally frozen modified nanocellulose aerogel.
[0030] In another aspect, the present invention also provides a use of the modified nanocellulose aerogel as described above in oil-water separation.
[0031] The modified nanocellulose aerogel of the present invention has good hydrophobicity and can be used for oil-water separation, especially has good adsorption performance for chlorinated alkanes. In addition, it has good flame retardant performance. In addition, it has low thermal conductivity and good thermal insulation performance. The preparation method of the present invention can obtain a modified nanocellulose aerogel having good adsorption performance for oil, good flame retardant performance and good thermal insulation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the infrared spectrum of PVTMS obtained in Preparation Example 1.
[0033] Figure 2(a) shows uP 2.5 Thermal infrared image of the temperature of T aerogel on a 100°C heating plate versus time.
[0034] Figure 2(b) shows bP 2.5 Thermal infrared image of the temperature of T aerogel on a 100°C heating plate versus time.
[0035] Figure 3(a) shows uP 2.5 T aerogel separation process of dichloromethane / water.
[0036] Figure 3(b) shows uP 2.5 T aerogel separation process of n-hexane / water.
[0037] Figure 4(a) shows the aerogel uP formed by unmodified oxidized nanocellulose fibers 0.0 T's combustion performance test process.
[0038] Figure 4(b) shows bP 5.0 The combustion performance test process of T aerogel.
[0039] Figure 5 Schematic diagram of the structure of the freezing equipment including the freezing platform used for freeze drying the gel product in Examples 1 to 4.
[0040] Figure 6 Schematic diagram of the structure of the freezing equipment including the freezing tank used for freeze drying the gel product in Examples 5 to 8.
[0041] Description of reference numerals:
[0042] 1-liquid nitrogen container, 2-copper column, 3-first platform, 10-glass mold; 4-second platform, 41-groove. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0044] <Modified Nanocellulose Aerogel>
[0045] The present invention provides a modified nanocellulose aerogel, which is formed by raw materials including a polymer shown in formula (1) and oxidized cellulose nanofibers, and the mass ratio of the polymer shown in formula (1) to the oxidized cellulose nanofibers is defined as m, and 1≤m<10. In certain specific embodiments, the modified nanocellulose aerogel of the present invention is formed only by the polymer shown in formula (1) and the oxidized cellulose nanofibers, and the mass ratio of the polymer shown in formula (1) to the oxidized cellulose nanofibers is defined as m, then 1≤m<10. Such modified nanocellulose aerogel has good hydrophobicity and can be used for oil-water separation, especially good adsorption of chlorinated alkanes, with a high adsorption amount of more than 60g / g. Furthermore, such modified nanocellulose aerogel has good flame retardant properties. In addition, such modified nanocellulose aerogel has a low thermal conductivity and good thermal insulation performance. It is safer when used.
[0046] The polymer represented by formula (1) is as follows:
[0047]
[0048] In formula (1), n is a natural number of 70 to 105, preferably a natural number of 70 to 95, more preferably a natural number of 72 to 85, and even more preferably a natural number of 74 to 80. Me is a methyl group.
[0049] In the present invention, the polymer represented by formula (1) can be obtained by reacting vinyltrimethoxysilane in the presence of tert-butyl peroxide.
[0050] In the present invention, the polymer represented by formula (1) can be referred to as polyvinyltrimethoxysilane.
[0051] In the present invention, the oxidized cellulose nanofibers have a structure as shown in formula (2):
[0052]
[0053] In formula (2), y is a natural number of 50 to 1000. Preferably, y is a natural number of 80 to 700. More preferably, y is a natural number of 80 to 300.
[0054] In the present invention, the oxidized cellulose nanofibers may be referred to as TOCNF. In the present invention, the oxidized cellulose nanofibers TOCNF may be oxidized cellulose nanofibers obtained by oxidizing cellulose nanofibers using TEMPO. The oxidation process may refer to the prior art. In the present invention, the diameter of the oxidized cellulose nanofibers may be 1 to 10 nm, and the length may be 0.1 to 2 μm. This is conducive to the formation of a modified nanocellulose aerogel material that takes into account lower thermal conductivity, flame retardancy and adsorption properties.
[0055] In the present invention, the mass ratio of the polymer represented by formula (1) to the oxidized cellulose nanofiber is defined as m, then 1≤m<10, preferably, 1.5≤m<7, more preferably, 1.5≤m<6, and even more preferably, 2≤m≤5. For example, m may be 2, 2.5, 3.0, 3.5, 4.0, 4.5, or 5.0.
[0056] In the present invention, the average thermal conductivity of the modified nanocellulose aerogel is less than 50 mW·m -1 ·K -1 , preferably less than or equal to 48mW·m -1 ·K -1 And greater than or equal to 35mW·m -1 ·K -1 .
[0057] In the present invention, the contact angle of the modified nanocellulose aerogel is greater than 100°, preferably greater than or equal to 105°, more preferably greater than or equal to 110°, for example, greater than or equal to 115°, and even greater than or equal to 127°.
[0058] In the present invention, the modified nanocellulose aerogel has good adsorption performance for oil, and the oil includes an organic solvent with a lower density than water and an organic solvent with a higher density than water. Organic solvents with a lower density than water include but are not limited to ethyl acetate, acetonitrile, toluene, and cyclohexane. Organic solvents with a higher density than water include but are not limited to chlorinated alkanes, and chlorinated alkanes may include methylene chloride, ethylene dichloride, and chloroform. The adsorption capacity of cyclohexane can be 23g / g and can reach 34g / g. The adsorption capacity of methylene chloride can be 52g / g and reach 67g / g. The adsorption capacity of ethylene dichloride can be 48g / g and can reach 63g / g.
[0059] <Preparation method>
[0060] The present invention also provides a method for preparing the modified nanocellulose aerogel as above, comprising the following steps: 1) a raw material mixing step; 2) an acid pH adjustment step; 3) a gel product forming step; 4) a modified nanocellulose aerogel forming step. Optionally, it also comprises a step of preparing a polymer represented by formula (1). The following is a detailed description.
[0061] Preparation steps of the polymer represented by formula (1)
[0062] In the present invention, the polymer described in formula (1) is obtained by reacting vinyltrimethoxysilane in the presence of tert-butyl peroxide.
[0063] The reaction can be carried out in an autoclave, preferably in a hydrothermal autoclave. The reaction temperature is 100 to 150° C., preferably 110 to 140° C., more preferably 120 to 130° C. The reaction time can be 10 to 56 hours, preferably 20 to 56 hours, more preferably 30 to 50 hours.
[0064] In the present invention, the mass ratio of tert-butyl peroxide to vinyltrimethoxysilane is 1:8-15, preferably 1:9-13, and more preferably 1:10-12.
[0065] In the present invention, the tert-butyl peroxide can be selected from one of tert-butyl hydroperoxide (TBHP), di-tert-butyl peroxide (DTBP), and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (DHBP). Preferably, the tert-butyl peroxide is di-tert-butyl peroxide (DTBP).
[0066] Raw material mixing steps
[0067] The polymer represented by formula (1) and the oxidized cellulose nanofiber suspension are placed in an alkane solvent and mixed to obtain a mixture, which is conducive to obtaining a modified nanocellulose fiber aerogel with good adsorption performance.
[0068] In the present invention, the ratio of the amount of the polymer represented by formula (1) to the amount of the oxidized cellulose nanofibers in the oxidized cellulose nanofiber suspension is as described above.
[0069] In the present invention, the oxidized cellulose nanofiber suspension may also be referred to as an oxidized cellulose nanofiber dispersion, which is a dispersion of oxidized cellulose nanofibers in water. The mass concentration of the oxidized cellulose nanofiber suspension is 1-2 wt%, preferably 1-1.9 wt%, and more preferably 1.1-1.9 wt%.
[0070] In the present invention, the alkane solvent is selected from C5-C10 alkanes, which refer to alkanes having 5 to 10 carbon atoms. Examples of C5-C10 alkanes include, but are not limited to, n-pentane, n-hexane, cyclohexane, n-heptane, n-octane, and the like.
[0071] According to a specific embodiment of the present invention, the alkane solvent is cyclohexane.
[0072] In certain embodiments, the polymer represented by formula (1), the oxidized cellulose nanofiber suspension, and water are placed in an alkane solvent and mixed to obtain a mixture. The water may be deionized water, purified water, or distilled water.
[0073] The mass ratio of the polymer represented by formula (1), the alkane solvent, and water is 1-10:5-8:15-25, preferably 1-8:6-7:16-22, and more preferably 1-6:6-7:20-22.
[0074] In the present invention, during mixing, vigorous stirring may be performed to obtain a mixture.
[0075] Acid pH Adjustment Steps
[0076] The mixture is adjusted to a pH value of less than 7 with an acid to obtain an emulsion. This is conducive to obtaining a modified nanocellulose aerogel with good adsorption performance.
[0077] In the present invention, the acid can be selected from hydrochloric acid, sulfuric acid, and nitric acid, preferably nitric acid. The mass concentration of the acid can be 1-10wt%, preferably 3-8wt%, more preferably 5-7wt%. The pH value is adjusted to 5-6.
[0078] According to a specific embodiment of the present invention, the mixture is adjusted to a pH value of 6 with an acid, and then allowed to stand for 1 to 3 hours to obtain a stable emulsion.
[0079] Gel product formation steps
[0080] The emulsion is adjusted to a pH value greater than or equal to 8 with an alkali, and allowed to stand to form a gel product. This is beneficial to promoting gelation and obtaining a modified nanocellulose aerogel with good adsorption performance. The alkali is preferably a quaternary ammonium alkali.
[0081] According to a specific embodiment of the present invention, the quaternary ammonium base is tetramethylammonium hydroxide.
[0082] According to one embodiment of the present invention, the emulsion is adjusted to a pH value of 9 to 10 with a quaternary ammonium base and allowed to stand for 8 to 20 hours to form a gel product. The standing time is preferably 10 to 15 hours, more preferably 12 to 15 hours.
[0083] Modified nanocellulose aerogel formation steps
[0084] The gel product is freeze-dried to obtain a lyophilized product; the lyophilized product is heated and dried to obtain a modified nanocellulose aerogel.
[0085] In the present invention, the freeze drying temperature is less than -30°C, preferably less than or equal to -40°C, more preferably less than or equal to -50°C. The heating drying temperature may be greater than or equal to 45°C, preferably 50 to 70°C, more preferably 60 to 65°C.
[0086] In the present invention, when freezing the gel product, it is preferred to control the direction of heat conduction.
[0087] In certain embodiments, the gel product is placed in a mold, and the mold is placed above a freezing platform so that the heat conduction direction of the gel product is vertical, and the product is freeze-dried at a temperature below -50°C to obtain a freeze-dried product; the freeze-dried product is heated and dried to obtain a unidirectionally frozen modified nanocellulose aerogel. In this way, an anisotropic aerogel can be obtained, which has good adsorption performance, flame retardancy and heat insulation performance.
[0088] In the present invention, the freezing platform is a platform after the temperature is reduced, and its shape is not particularly limited, and it can be a rectangular structure. The freezing platform has good thermal conductivity and can be made of copper material, which is used to freeze-dry the gel product in the mold and is conducive to controlling the direction of heat conduction. The mold can be a glass mold.
[0089] In other embodiments, the gel product is directly placed in a freezing tank with an upper opening so that the heat conduction direction for freezing the gel product is vertical and horizontal, and freeze-dried below -50°C to obtain a freeze-dried product; the freeze-dried product is heated and dried to obtain a bidirectionally frozen modified nanocellulose aerogel. In this way, an anisotropic aerogel can be obtained, which has good adsorption performance, flame retardant performance and heat insulation performance.
[0090] In the present invention, the freezing tank can be a groove after cooling, and the freezing tank can be a groove formed on a platform with good thermal conductivity, and the material can be copper. It is used to freeze-dry the gel product and is conducive to controlling the direction of heat conduction. The platform can be a rectangular parallelepiped structure.
[0091] In certain specific embodiments, the gel product is placed in a glass mold, the glass mold is placed on a first platform (i.e., a freezing platform) above the top of the metal column, and at least most of the metal column is immersed in a freezing medium container containing a freezing medium, the first platform is located above the liquid surface of the freezing medium, so that the heat conduction direction for freezing the gel product is vertical, and freeze-dried below -50°C to obtain a lyophilized product; the lyophilized product is heated and dried to obtain a unidirectionally frozen modified nanocellulose aerogel. The freezing medium can be liquid nitrogen.
[0092] In other specific embodiments, the gel product is directly placed in the groove (i.e., freezing tank) of the second platform above the top of the metal column, the opening of the groove faces upward, and at least most of the metal column is immersed in a freezing medium container containing a freezing medium, and the second platform is located above the liquid surface of the freezing medium, so that the heat conduction direction of freezing the gel product is vertical and horizontal, and freeze-dried below -50°C to obtain a lyophilized product; the lyophilized product is heated and dried to obtain a bidirectionally frozen modified nanocellulose aerogel. The freezing medium can be liquid nitrogen.
[0093] In the present invention, the metal pillar, the first platform and the second platform have good thermal conductivity, for example, they can all be made of copper.
[0094] <Purpose>
[0095] The present invention also provides a use of the modified nanocellulose aerogel as described above in oil-water separation. The modified nanocellulose aerogel of the present invention has good hydrophobicity and good adsorption for organic solvents with a density greater than water and organic solvents with a density less than water. The present invention particularly provides a use of the modified nanocellulose aerogel as described above in the separation of chloroalkanes and water.
[0096] The modified nanocellulose aerogel of the present invention can adsorb 52 g / g to 67 g / g of dichloromethane, and 48 g / g to 63 g / g of ethylene dichloride.
[0097] In the following examples, the TOCNF suspension is an oxidized nanocellulose fiber suspension purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd.
[0098] Preparation Example 1
[0099] 10 parts by weight of vinyl trimethoxysilane and 1 part by weight of di-tert-butyl peroxide (DTBP) were added to a hydrothermal kettle, sealed, and then reacted at 120° C. for 48 hours to obtain polyvinyl trimethoxysilane, which was recorded as PVTMS.
[0100] The infrared spectrum of the obtained polyvinyltrimethoxysilane is shown in Figure 1 The molecular weight of the obtained polyvinyltrimethoxysilane was 10,000 and the degree of polymerization was 74.
[0101] Example 1
[0102] 0.2 g of PVTMS prepared in Preparation Example 1, 10.7 g of a TOCNF suspension having a mass concentration of 1.87 wt% (including 0.2 g of TOCNF) and 20.0 g of deionized water were sequentially added to 7.0 g of cyclohexane to obtain a mixture, wherein the mass ratio of PVTMS to TOCNF was 1:1.
[0103] The mixture was vigorously stirred for 2 minutes, and then nitric acid with a mass concentration of 5 wt % was added dropwise thereto to adjust the pH value of the mixture to 6 to form an emulsion, which was allowed to stand for 2 hours.
[0104] Then, tetraammonium hydroxide (TMAOH) was added dropwise to the emulsion after standing to adjust the pH value to 8, and then the emulsion was allowed to stand for 12 hours to obtain a gel product.
[0105] The gel product was transferred to a glass mold and the bubbles were eliminated using ultrasound. Figure 5 As shown, a freezing device including a freezing platform is provided, and the freezing device includes a liquid nitrogen container 1, a copper column 2 and a first platform 3 (the first platform 3 is the freezing platform). Liquid nitrogen is contained in the liquid nitrogen container 1. The copper column 2 is arranged vertically, and a first platform 3 is arranged above the top thereof, and most of the copper column 2 is immersed in liquid nitrogen. The first platform 3 is above the liquid surface of liquid nitrogen. The material of the first platform 3 is copper, and the first platform 3 can be a rectangular parallelepiped structure. A glass mold 10 containing a gel product is placed on the first platform 3 above the top of the copper column 2, so that the heat conduction direction for freezing the gel product is in a vertical direction (i.e., perpendicular to the bottom surface direction of the gel product), and the gel product is freeze-dried at -50°C for 3 days. A freeze-dried product is obtained.
[0106] The freeze-dried product was placed in an oven and heated and dried at 60°C for 2 hours to obtain a modified nanocellulose aerogel, which was a unidirectionally frozen PVTMS / TOCNF hybrid aerogel, denoted as uP 1.0 T.
[0107] Example 2
[0108] The only difference from Example 1 is that the mass ratio of PVTMS to TOCNF is 2.5:1. The obtained modified nanocellulose aerogel is denoted as uP 2.5 T.
[0109] Example 3
[0110] The only difference from Example 1 is that the mass ratio of PVTMS to TOCNF is 3.5:1. The obtained modified nanocellulose aerogel is denoted as uP 3.5 T.
[0111] Example 4
[0112] The only difference from Example 1 is that the mass ratio of PVTMS to TOCNF is 5.0:1. The obtained modified nanocellulose aerogel is denoted as uP 5.0 T.
[0113] Example 5
[0114] 0.2 g of PVTMS prepared in Preparation Example 1, 10.7 g of a TOCNF suspension having a mass concentration of 1.87 wt% (including 0.2 g of TOCNF) and 20.0 g of deionized water were sequentially added to 7.0 g of cyclohexane to obtain a mixture, wherein the mass ratio of PVTMS to TOCNF was 1:1.
[0115] The mixture was vigorously stirred for 2 minutes, and then nitric acid with a mass concentration of 5 wt % was added dropwise thereto to adjust the pH value of the mixture to 6 to form an emulsion, which was allowed to stand for 2 hours.
[0116] Then, tetraammonium hydroxide (TMAOH) was added dropwise to the emulsion after standing to adjust the pH value to 8, and then the emulsion was allowed to stand for 12 hours to obtain a gel product.
[0117] Reference Figure 6 As shown, a freezing device including a freezing tank is provided, the freezing device includes a liquid nitrogen container 1, a copper column 2, and a second platform 4. A groove 41 is provided on the second platform 3 (the groove 41 is the freezing tank), and the groove 41 can be used to accommodate the gel product. The liquid nitrogen container 1 is filled with liquid nitrogen. The copper column 2 is vertically arranged, and the second platform 4 is arranged on the top thereof, and most of the copper column 2 is immersed in the liquid nitrogen. The second platform 4 is located above the liquid surface of the liquid nitrogen. The material of the second platform 4 is copper.
[0118] The gel product was directly poured into the groove 41 (i.e., freezing tank) of the second platform 4 above the top of the copper column 2, so that the heat conduction direction for freezing the gel product was vertical and horizontal, and freeze-dried at -50°C for 3 days to obtain a lyophilized product.
[0119] The freeze-dried product was placed in an oven and heated and dried at 60°C for 2 hours to obtain a modified nanocellulose aerogel, which was a bidirectionally frozen PVTMS / TOCNF hybrid aerogel, denoted as bP 1.0 T.
[0120] Example 6
[0121] The only difference from Example 5 is that the mass ratio of PVTMS to TOCNF is 2.5:1. The obtained modified nanocellulose aerogel is denoted as bP 2.5 T.
[0122] Example 7
[0123] The only difference from Example 5 is that the mass ratio of PVTMS to TOCNF is 3.5:1. The obtained modified nanocellulose aerogel is denoted as bP 3.5 T.
[0124] Example 8
[0125] The only difference from Example 5 is that the mass ratio of PVTMS to TOCNF is 5.0:1. The obtained modified nanocellulose aerogel is denoted as bP 5.0 T.
[0126] Performance testing and evaluation experiments
[0127] The modified nanocellulose aerogels obtained in the examples were subjected to performance evaluation experiments.
[0128] (I) Testing of thermal conductivity and thermal insulation performance
[0129] Thermal conductivity test method: refer to the thermal conductivity test method given in CN113583302A. The test results are shown in Table 1.
[0130] Table 1
[0131] sample <![CDATA[Average thermal conductivity (mW·m -1 ·K -1 )]]> <![CDATA[u-P 1.0 T]]> 39.1 <![CDATA[u-P 2.5 T]]> 37.7 <![CDATA[u-P 3.5 T]]> 36.7 <![CDATA[u-P 5.0 T]]> 39.7 <![CDATA[b-P 1.0 T]]> 47.7 <![CDATA[b-P 2.5 T]]> 46.8 <![CDATA[b-P 3.5 T]]> 41.4 <![CDATA[b-P 5.0 T]]> 45.9
[0132] It can be seen from Table 1 that the obtained modified nanocellulose aerogel has a low average thermal conductivity and good thermal insulation performance.
[0133] Thermal insulation performance test: Use thermal imaging camera (Hikvision DS-2TPH10-3AUF) to test. 2.5 T and bP 2.5 The thermal infrared results of the temperature change of T aerogel on a 100°C heating plate are shown in Figure 2(a) and Figure 2(b). It can be further seen from Figure 2(a) and Figure 2(b) that the thermal insulation performance of the modified nanocellulose aerogel is good.
[0134] (B) Contact angle test
[0135] Test method: The contact angle of modified nanocellulose aerogel with water was tested at room temperature using a contact angle interfacial tension tester (Kruss DSA30S, Germany). The test results are shown in Table 2.
[0136] Table 2
[0137] sample <![CDATA[u-P 0.0 T]]> <![CDATA[u-P 1.0 T]]> <![CDATA[u-P 2.5 T]]> <![CDATA[u-P 3.5 T]]> <![CDATA[u-P 5.0 T]]> <![CDATA[b-P 1.0 T]]> <![CDATA[b-P 2.5 T]]> <![CDATA[b-P 3.5 T]]> <![CDATA[b-P 5.0 T]]> Contact angle 0 105.5 127.1 112.4 115.7 104.6 115.6 130.1 124.5
[0138] As shown in Table 2, the contact angle of the modified nanocellulose aerogel obtained by the present invention is large, and the hydrophobic property is good. The contact angle of the unmodified oxidized nanocellulose fiber aerogel is 0°, and the hydrophilicity is good.
[0139] (III) Adsorption of organic solvents (oils)
[0140] The test method is as follows:
[0141] First, accurately weigh the mass of the modified nanocellulose aerogel sample. Completely immerse the weighed aerogel sample in a container filled with the selected organic solvent. The size of the container should ensure that the organic solvent can completely cover the aerogel sample. Let the aerogel sample soak in the organic solvent for a period of time, usually 7 or 8 minutes, to ensure that it reaches adsorption equilibrium. Use tweezers or other tools to remove the adsorption-saturated aerogel sample from the organic solvent, and gently drain (absorb) the solvent on its surface with filter paper. Weigh again. By comparing the mass difference before and after adsorption, the amount of organic solvent adsorbed by the modified nanocellulose aerogel can be calculated.
[0142] The test results are shown in Table 3. Table 3 is uP 2.5 T aerogel and bP 2.5 T Aerogel unit adsorption capacity of various oils. Unit: g·g -1 Has the same meaning as g / g.
[0143] Table 3
[0144]
[0145] As can be seen from Table 3, the modified nanocellulose aerogel of the present invention has a large adsorption capacity for organic solvents. Each gram of modified nanocellulose aerogel can adsorb more than 29 grams of acetonitrile, more than 52 grams of dichloromethane, and more than 48 grams of dichloroethane. The adsorption capacity of dichloroethane can even reach 63 g / g, and the adsorption capacity of dichloromethane can reach 67 g / g.
[0146] (IV) Application in oil-water separation
[0147] Testing uP2.5 The separation process of dichloromethane / water and hexane / water by T aerogel is shown in Figure 3(a) and Figure 3(b) respectively. 2.5 The T aerogel can separate dichloromethane from water, separate n-hexane from water, and leave the water in the uP 2.5 T aerogel, indicating uP 2.5 T aerogel has good hydrophobicity and good lipophilicity to dichloromethane and n-hexane.
[0148] (V) Flame retardant performance test
[0149] Flame retardant performance test method 1: Use alcohol lamp to carry out combustion test, the results are shown in Figure 4 (a) and Figure 4 (b). Figure 4 (a) is the unmodified aerogel uP 0.0 Figure 4(b) shows the combustion test process of bP 5.0 The combustion test process of T aerogel. It can be seen that the flame retardant properties of the aerogel formed by the unmodified oxidized nanocellulose fibers are poor. The flame retardant properties of the modified nanocellulose aerogel are good.
[0150] Flame retardant test method 2: The combustion process was evaluated using a cone calorimeter (FTT i-Cone, UK) with a sample diameter of 100 mm, a height of 10 mm, and a radiation intensity of 35 kW / m 2 The test results are shown in Table 4.
[0151] Table 4
[0152]
[0153] It can be seen from Table 4 that, compared with the aerogel formed by unmodified oxidized nanocellulose fibers, the modified nanocellulose aerogel of the present invention has a smaller total heat release and better flame retardant properties.
[0154] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be thought of by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A modified nanocellulose aerogel, characterized in that: It is formed from raw materials including a polymer represented by formula (1) and oxidized cellulose nanofibers, wherein the mass ratio of the polymer represented by formula (1) to the oxidized cellulose nanofibers is denoted as m, and 1≤m<10; In formula (1), n is a natural number of 70 to 105, and Me is a methyl group.
2. The modified nanocellulose aerogel according to claim 1, characterized in that The oxidized cellulose nanofiber has a structure as shown in formula (2): In formula (2), y is a natural number ranging from 50 to 1000.
3. The modified nanocellulose aerogel according to claim 1, characterized in that The contact angle is greater than or equal to 100°.
4. A method for preparing the modified nanocellulose aerogel according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) placing the polymer represented by formula (1) and the oxidized cellulose nanofiber suspension in an alkane solvent and mixing them to obtain a mixture; 2) adjusting the pH value of the mixture to less than 7 with an acid to obtain an emulsion; 3) adjusting the pH value of the emulsion to be greater than or equal to 8 with an alkali, and allowing to stand to form a gel product; 4) freeze-drying the gel product to obtain a freeze-dried product; heating and drying the freeze-dried product to obtain a modified nanocellulose aerogel.
5. The preparation method according to claim 4, characterized in that: In step 1), the polymer represented by formula (1) is obtained by reacting vinyltrimethoxysilane in the presence of tert-butyl peroxide; wherein the reaction is carried out in a hydrothermal kettle, the reaction temperature is 100-150° C., and the mass ratio of tert-butyl peroxide to vinyltrimethoxysilane is 1:8-15.
6. The preparation method according to claim 4, characterized in that: Step 1) comprises the following specific steps: placing the polymer represented by formula (1), oxidized cellulose nanofiber suspension and water in an alkane solvent and mixing them to obtain a mixture; wherein the mass concentration of the oxidized cellulose nanofiber suspension is 1 to 2 wt%; and the alkane solvent is selected from C5 to C10 alkanes.
7. The preparation method according to claim 4, characterized in that: In step 2), the acid is selected from hydrochloric acid, sulfuric acid or nitric acid; in step 3), the base is a quaternary ammonium base.
8. The preparation method according to claim 4, characterized in that: In step 4), the freeze drying temperature is less than -30°C, and the heating drying temperature is greater than or equal to 45°C.
9. The preparation method according to claim 8, characterized in that: Step 4) is specifically selected from any one of the following steps: (a) placing the gel product in a mold, placing the mold above a freezing platform so that the heat conduction direction for freezing the gel product is in a vertical direction, and freeze-drying the gel product below -50°C to obtain a freeze-dried product; heating and drying the freeze-dried product to obtain a unidirectionally frozen modified nanocellulose aerogel; (b) placing the gel product directly in a freezing tank having an upper opening so that the heat conduction direction for freezing the gel product is vertical and horizontal, and freeze-drying the product below -50°C to obtain a freeze-dried product; heating and drying the freeze-dried product to obtain a bidirectionally frozen modified nanocellulose aerogel.
10. Use of the modified nanocellulose aerogel according to any one of claims 1 to 3 in oil-water separation.
Citation Information
Patent Citations
Preparation method of super-hydrophobic cellulose aerogel and application of super-hydrophobic cellulose aerogel in oil stain treatment
CN104710647A
Super-hydrophobic organic silicon aerogel as well as normal-temperature and normal-pressure drying preparation method and application thereof
CN111253615A
Adsorption material as well as preparation method and application thereof
CN113578286A
Thermal insulation material and preparation method thereof
CN113583302A